2020
DOI: 10.4132/jptm.2020.06.23
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node size and its association with nodal metastasis in ductal adenocarcinoma of the pancreas

Abstract: Background: Although lymph node metastasis is a poor prognostic factor in patients with pancreatic ductal adenocarcinoma (PDAC), our understanding of lymph node size in association with PDAC is limited. Increased nodal size in preoperative imaging has been used to detect node metastasis. We evaluated whether lymph node size can be used as a surrogate preoperative marker of lymph node metastasis. Methods: We assessed nodal size and compared it to the nodal metastatic status of 200 patients with surgically resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Unfortunately, tools routinely used for the radiological staging of PDAC (e.g., CT scan, MRI, etc.) are impaired by a not negligible rate of down-staged tumors; notably, a lack of sensitivity in nodal involvement assessment is usually reported [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, tools routinely used for the radiological staging of PDAC (e.g., CT scan, MRI, etc.) are impaired by a not negligible rate of down-staged tumors; notably, a lack of sensitivity in nodal involvement assessment is usually reported [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, it has been widely reported that even if nodal positivity is one of the main factors influencing the prognosis of PDAC patients, there are limited possibilities for identifying positive lymphnodes with common radiological investigations. These tools offer information regarding the size and the morphology of the lymphnodes, but, as reported by Shin, the accuracy of preoperative radiologic imaging to assess N+ is poor (36).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, regional LN metastasis detected on preoperative imaging was a significant risk factor for early tumor recurrence, which is consistent with previous reports 13 , 15 . However, the preoperative identification of regional LN metastasis on imaging studies remains challenging due to the lack of consensus on the diagnostic criteria and overall low sensitivity 20 , 21 , 23 , 26 . Our results showed that both the LN OR and LN AND definitions provided sensitivity, specificity, PPV, NPV, and accuracy which fell within the range of previous reports 2 , 27 – 30 .…”
Section: Discussionmentioning
confidence: 99%